Portrait of the kings : the Davidic prototype in Deuteronomistic poetics - Joseph, Alison L. (Minneapolis: : Fortress Press, 2015)
Much of the scholarship on the book of Kings has focused on questions of the historicity of the events described. Alison L. Joseph turns her attention instead to the literary characterization of Israel's kings. By examining the narrative techniques used in the Deuteronomistic History to portray Israel's kings, Joseph shows that the Deuteronomist in the days of the Josianic Reform constructed David as a model of adherence to the covenant, and Jeroboam, conversely, as the ideal opposite of David. The redactor further characterized other kings along one or the other of these two models. The resulting narrative functions didactically, as if instructing kings and the people of Judah regarding the consequences of disobedience. Attention to characterization through prototype also allows Joseph to identify differences between pre-exilic and exilic redactions in the Deuteronomistic History, bolstering and also revising the view advanced by Frank Moore Cross. The result is a deepened understanding of the worldview and theology of the Deuteronomistic historians.
The Davidic prototype in historiographical poetics of the Deueteronomist -- The historiographical poetics of the preexilic Deuteronomist -- David "who observed my commandments ..." -- Jeroboam "who caused Israel to sin" -- Josiah : "no one arose like him" -- Manasseh "who did more evil than all ... who were before him" : a counterexample -- Conclusion : "there shall be a king over us."
Revision of the author's thesis (Ph. D. in Near Eastern Studies)--University of California, Berkeley, 2012 under title: The portrait of the kings and the historiographical poetics of the Deuteronomistic historian.
Includes bibliographical references (pages 239-255) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Deuteronomistic history (Biblical criticism); Kings and rulers -- Biblical teaching